Association of myocardial and liver T2* iron measurements with systolic and diastolic function by CMR feature tracking strain analysis - Quezada-Pinedo, Hugo G.; Bernhard, Benedikt; Zurkirchen, Jan C.; Stark, Anselm W.; Ahanchi, Noushin Sadat; Gebhard, Catherine; Ott, Daniel; Peters, Alan A.; von Tengg-Kobligk, Hendrik; Schütze, Jonathan; Bakula, Adam; Wahl, Andreas; et al. (Frontiers in Cardiovascular Medicine, 2025)
Background/ObjectivesMyocardial and liver iron overload can be assessed through T2* in magnetic resonance imaging (MRI). It is unclear, how T2* measurements are associated with systolic and diastolic left ventricular function assessed by novel feature tracking (FT) strain.MethodsConsecutive patients with suspected iron overload undergoing MRI T2* were retrospectively included. T2* was studied continuously and in categories: normal myocardial iron status (T2* ≥ 20 ms), myocardial iron overload (T2* < 20 ms), normal liver iron status (T2* ≥ 15.4 ms) and liver iron overload (T2* < 15.4 ms). Multivariable regression models were used to assess associations between T2* and FT strain.ResultsAmong 172 participants, longitudinal e/a ratio [−0.17 (−0.27, −0.08), p = 0.001], longitudinal early diastolic strain rate [−0.13 (−0.23, −0.03), p = 0.014], circumferential late diastolic strain rate [0.18 (0.03, 0.32), p = 0.016], longitudinal late diastolic strain rate [0.20 (0.03, 0.36), p = 0.019] were associated with higher T2*. Liver iron overload was associated with circumferential systolic strain rate [−0.42 (−0.74, −0.09), p = 0.014] and longitudinal early diastolic strain rate [0.27 (0.04, 0.49), p = 0.023]. Combined liver and myocardial iron overload were associated with longitudinal e/a ratio [0.72 (0.19, 1.24), p = 0.008]. No associations of T2* values with systolic function were found.ConclusionLiver and a combination of myocardial and liver iron overload were associated with increased early diastolic filling and increased e/a ratio respectively, which may serve as markers of diastolic dysfunction. Impaired diastolic function, even in the absence of myocardial iron overload was associated with liver iron metabolism and may indicate early cardiac involvement, while left ventricular systolic function is still preserved.